2023
DOI: 10.3390/antibiotics12010101
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure among Honey Samples of Different Pollen Origin

Abstract: Honey’s antibacterial activity has been recently linked to the inhibitory effects of honey microbiota against a range of foodborne and human pathogens. In the current study, the microbial community structure of honey samples exerting pronounced antimicrobial activity was examined. The honey samples were obtained from different geographical locations in Greece and had diverse pollen origin (fir, cotton, fir–oak, and Arbutus unedo honeys). Identification of honey microbiota was performed by high-throughput ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…The ability to investigate the bee gut microbiota from honey samples may serve as an additional tool for monitoring the health of bee colonies 8,9,77 . The gut microbiota of adult honey bees are observed to be low complexity communities, with the composition of the microbial communities influenced by diet 78 as well as through social interactions with other members of the hive 79,80 .…”
Section: Colony Health Monitoring Uncovers Ecological Interactions An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to investigate the bee gut microbiota from honey samples may serve as an additional tool for monitoring the health of bee colonies 8,9,77 . The gut microbiota of adult honey bees are observed to be low complexity communities, with the composition of the microbial communities influenced by diet 78 as well as through social interactions with other members of the hive 79,80 .…”
Section: Colony Health Monitoring Uncovers Ecological Interactions An...mentioning
confidence: 99%
“…Aside from bee-related taxa, honey was also found to contain genetic information from animal-and plant-associated microorganisms containing both beneficial and pathogenic species 77 . This presents a critical avenue to explore and monitor the environmental microbiome for deleterious changes that could threaten biodiversity within an ecosystem of interest 87 .…”
Section: Colony Health Monitoring Uncovers Ecological Interactions An...mentioning
confidence: 99%
“…The European Union (EU) is the second biggest (after China) honey producer worldwide. Spain, Romania, Greece, Poland, France, and Italy are the major honey-producing EU countries [54]. Both honey bees and stingless bees produce honey as the main carbohydrate nutritional source [5,55].…”
Section: Honeymentioning
confidence: 99%
“…They suggested that low oxygen levels in honey might affect the structure of the microbial community. Overall, the investigated honey microbiota comprised bacteria present in the bee gut, both beneficial bacteria (probiotics) as well as pathogenic microbes of botanical origin [54].…”
Section: Honey Microbiomementioning
confidence: 99%
“…In fact, they detected 335 distinct taxa in honey microbiota, native to the gut microbiota of melliferous bees and microbiota of their flowering plants, including beneficial bacteria like probiotic strains. These could work as indicators of the authenticity of honey, facilitating the identification of honey samples with potent antimicrobial profiles [8]. β-Glucan is an important natural prebiotic abundant in lentinan, cereals and the yeast cell wall.…”
mentioning
confidence: 99%